2005
DOI: 10.1093/jac/dki324
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of SHV-12 and CTX-M-type extended-spectrum β-lactamases among clinical isolates of Escherichia coli and Klebsiella pneumoniae and emergence of GES-3 in Korea

Abstract: CTX-M-type and/or SHV-12 ESBL-producing E. coli and K. pneumoniae isolates are spreading, and a GES-type ESBL has emerged in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 7 publications
3
76
3
2
Order By: Relevance
“…[33][34][35] In contrast, in agreement with our data, Russian, Cameroonian, and Korean studies revealed that overall prevalence of ESBLs among E. coli isolates was 15.8%, 14.3%, and 9.3%, respectively. [36][37][38] Studies conducted by Akram and others 17 showed a higher percentage, than our study, of E. coli producing ESBL. Prior antibiotics, especially ciprofloxacin, third-generation cephalosporins, and stay in hospital; major risk factors retained in our multivariate analysis, were also found to be independent risk factors for ESBL positivity in previous studies.…”
Section: 17contrasting
confidence: 46%
“…[33][34][35] In contrast, in agreement with our data, Russian, Cameroonian, and Korean studies revealed that overall prevalence of ESBLs among E. coli isolates was 15.8%, 14.3%, and 9.3%, respectively. [36][37][38] Studies conducted by Akram and others 17 showed a higher percentage, than our study, of E. coli producing ESBL. Prior antibiotics, especially ciprofloxacin, third-generation cephalosporins, and stay in hospital; major risk factors retained in our multivariate analysis, were also found to be independent risk factors for ESBL positivity in previous studies.…”
Section: 17contrasting
confidence: 46%
“…The prevalence of SHV, TEM and CTX-M among the ESBL-producers was 91, 71 and 36.4 %, respectively. In the SHV group, the variants SHV-12 and SHV-5 were the most prevalent, as is the case worldwide (Paterson et al, 2003;Villegas et al, 2008;Ryoo et al, 2005). Other non-ESBL SHVs were also detected at lower rates, including SHV-1, SHV-11 and SHV-85, found in six, four and two isolates, respectively.…”
Section: Enterobacteriaceaementioning
confidence: 88%
“…The isolates were identified with API-20 E systems (bioMérieux, Marcy l'Etoile, France). Searches for genes coding for the class A ESBLs and pAmpCs were performed by PCR amplification as described previously (7,8). The PCR products were subjected to direct sequencing.…”
Section: Methodsmentioning
confidence: 99%